If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + -2t = 7 Solving 19 + -2t = 7 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -2t = 7 + -19 Combine like terms: 19 + -19 = 0 0 + -2t = 7 + -19 -2t = 7 + -19 Combine like terms: 7 + -19 = -12 -2t = -12 Divide each side by '-2'. t = 6 Simplifying t = 6
| 7w+3=5(6w-11) | | 4x+67=9x+12 | | 10-10x=36-17x | | 2x+6=-102-10x | | 83-4x=2x+17 | | -16-5x=5-8x | | 6x+6=87-3x | | 2x+31=11x-59 | | 10x-22=5x+3 | | 8w+9=7(4w-8) | | 4x+44=7x+11 | | x^2-10x+12=0 | | 4w+6=6(2w-7) | | 4w+6= | | 3w+5= | | 97-7x=11x+15 | | 5-9x=17-16x | | -72-10x=9x+23 | | 2x^2-7x-8=0 | | 101-6x=10x+21 | | 2w+4=2(3w-8) | | 2+9x=90+x | | 4x+18=12x-78 | | 2x+50=6x+14 | | 12x+9=8x+21 | | 3+12x=36+x | | 4x+25=12x-71 | | 5(x+3)=2x | | 14-8X=36-22X | | 6c+1=4c+3 | | 67-5X=10X+20 | | 3X+6=-66-9X |